2022
DOI: 10.4102/sajhrm.v20i0.1888
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between transformational leadership, perceived organisational effectiveness and organisational culture in a selected multinational corporation in Africa

Abstract: Orientation: Multinational corporations (MNCs) in Africa are facing leadership, effectiveness and cultural challenges.Research purpose: The purpose was to determine the relationship between transformational leadership, perceived organisational effectiveness and organisational culture from the perspective of a MNC in Africa.Motivation of the study: Transformational leadership, organisational culture and perceived organisational effectiveness have been studied in different contexts, yet it is not clear how these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The advent of the COVID-19 pandemic has introduced an additional layer of complexity that organizations must navigate. Muzondiwa et al (2022) emphasize that despite some leaders perceiving crisis management as beyond their purview, fostering robust and resilient organizations in uncertainty necessitates a fresh mindset, which must emanate from upper management (Burlea et al, 2017). Once effective in a rapidly evolving world, certain leadership styles may need to be revised to address the current leadership challenges.…”
Section: Transformational Leadership (Tl)mentioning
confidence: 99%
See 4 more Smart Citations
“…The advent of the COVID-19 pandemic has introduced an additional layer of complexity that organizations must navigate. Muzondiwa et al (2022) emphasize that despite some leaders perceiving crisis management as beyond their purview, fostering robust and resilient organizations in uncertainty necessitates a fresh mindset, which must emanate from upper management (Burlea et al, 2017). Once effective in a rapidly evolving world, certain leadership styles may need to be revised to address the current leadership challenges.…”
Section: Transformational Leadership (Tl)mentioning
confidence: 99%
“…However, the findings could have been more consistent, leading to inconclusive results. While earlier studies by Gu et al (2018) and Chen et al (2014) have reported positive associations between transformational leadership and outcomes such as satisfaction and creativity, more recent research (Diana et al, 2021;Harijanti et al, 2021;Muzondiwa et al, 2022) has highlighted its positive influence on performance. This lack of consistency in the literature hampers theoretical advancements and impedes practitioners' ability to formulate clear strategic directions.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations